Analisis Faktor-Faktor yang Memengaruhi Penerapan Sistem Informasi Manajemen Rumah Sakit (SIMRS) di RSU Mamami Kupang - Damanik, Reinheart; Simon Sia Niha; Jou Sewa Adrianus; A. Manafe, Henny (Jurnal Ilmu Multidisiplin, 2023)
This study intends to analyze the factors that influence the implementation of the hospital management information system (SIMRS) at RSU MAMAMI Kupang. The results of inferential statistical analysis show that work culture has no significant impact on the implementation of the hospital management information system (SIMRS); age has no significant effect on the implementation of the hospital management information system (SIMRS); work experience does not have a significant impact on the implementation of the hospital management information system (SIMRS); Tool specifications affect meaningful implementation. The R square adjusted value shows that the coefficient of determination of the SIMRS application variable is 0.780 and the coefficient of determination of the HR Competency variable is 0.705. This value makes it clear that the involvement of work culture variables, age, work experience, HR competencies, tool specifications for the implementation of SIMRS is 78% and the contribution of work culture variables, age and work experience to HR competencies is 70%.